Categorizing numeric nutrients criteria and implications for water quality assessment in the Pearl River Estuary, China - Zhang, Peng; Ou, Shujun; Zhang, Junxiao; Zhao, Lirong; Zhang, Jibiao (Frontiers in Marine Science, 2022)
Coastal eutrophication, the over-enrichment of water with nutrients, has become a global ecological problem. As coastal waters are subjected to great pressure due to anthropogenic influences and climate change, establishing numeric nutrient criteria for coastal waters has been exceedingly complex at present. To control and improve the water quality of the Pearl River Estuary (PRE), based on the data from 2015 to 2020, the nutrient criteria of the PRE and adjacent waters were established using frequency statistical analysis. Based on the spatiotemporal salinity patterns, the coastal waters of the PRE were divided in three subareas namely freshwater (Zone I), mixed (Zone Ⅱ), and seawater (Zone III) using cluster analysis. The recommended criteria values of dissolved inorganic nitrogen (DIN) were 0.573, 0.312, and 0.134 mg·L-1 in Zones I, II, and III, respectively. The total nitrogen (TN) criterion for Zone Ⅲ (0.222 mg·L-1) was much lower than those for Zone Ⅰ (0.902 mg·L-1) and Zone Ⅱ (0.885 mg·L-1). The dissolved inorganic phosphorus (DIP) criteria were similar for the three Zones, 0.004−0.009 mg·L-1, whereas the total phosphorus (TP) recommended criteria in Zones I, II, and III were 0.039, 0.028, and 0.020 mg·L-1, respectively. In the water quality assessment, the categorizing numeric nutrients criteria can be referred and applied into fresh, mixed, and seawater zones of PRE. The results of this study provide a new nutrient reference condition in the PRE, which could be helpful in establishing integrated land-ocean unified nutrient criteria and water quality assessment, and implementing effective coastal eutrophication control in the future.